"Contra-mola que resiste” : as ocupações urbanas, da luta por moradia ao direito à cidade - Munhoz, Manoela Rodrigues (2020)
The present study aims to analyze how Urban Occupations become effective (or not) as strategies to access the right to housing in the central regions of the city of Porto Alegre, with a view to unveiling the contradictions of the phenomenon and contributing to the repertoire of struggle of the working class in the dispute for the right to the city. To this end, it was based on the dialectical-critical method, intending to analyze through the categories totality, historicity, contradiction, space and mediation the structure and dynamics of urban occupations as a strategy for the struggle of the working class. The research is of the qualitative-quantitative type, with an emphasis on qualitative data. The theoretical categories chosen as a priority, as a contribution to the reading and understanding of the investigated phenomenon are: Territory, housing issue, right to the city and urban occupations. A theoretical-bibliographic study was contemplated to identify the relevance of the theme of urban struggles in the production of knowledge of Social Work. To access the empirical data, the participant observation technique was used, with visits to active occupations in the central region of Porto Alegre and, due to their size and relevance, to the occupation People without Fear located in the metropolitan region of São Paulo. As research findings, it was identified the permanence of an insignificant production of Social Work in the debate about the repertoires of struggle of the working class. The theme of Urban Occupations was only found to be central in the productions of other areas of applied social sciences, with emphasis on Architecture and Urbanism. The research concluded that urban occupations carried out in the central regions of large cities are responsible for the most radical transformation of the repertoire of the struggle for housing in Brazil. They constitute collective actions that use the open gap - by the National Movement for Urban Reform - in the unconditionality of private property, which establishes the need to fulfill such a social function, and move forward, promoting actions that constrain the State to demonstrate in the face of illegality of real estate speculation, expressed by the revolting relationship between homeless people and idle properties. The radicality given by the occupations to the notions of the right to the city are evidenced by the dispute over the central spaces, privileged by their locality and by the accessibility to urban goods and services, but also, and mainly, by the relations they establish among themselves, in the construction of collective spaces sociability, income generation, political training, in addition to interactions with the city, by opening doors to the neighborhood and promoting cultural and festive events, attracting new partners and many militants, going back to experiences of “aggregation”, pointing out thus, alternatives for the subversion of the exclusive model of capitalist urbanization. From this conclusion, the following thesis was elaborated: The occupation of urban voids in central regions, as a strategy of resistance of the working class, are direct actions of a disruptive character that confront the contradictions of the urban issue. These actions, supported by the need to fulfill the social function of property, reveal the irrationality of organized cities for the reproduction of capital and the partiality of the State as a mediator of the irreconcilable interests of a society divided into classes. The collapse - material and symbolic - of fences erected by the exclusive urban model, is a sophisticated tool incorporated into the struggle for housing, which eliminates the boredom of homogenizing landscapes and calls for other life experiences in cities.